Outcome of Laser Surgery and Radiotherapy in Early Laryngeal Cancer - Rahman, Md Mostafizur; Siddiquee, Belayat Hossain; Karim, Md Afzal; Rahman, Tawfiqur; Nihar, Fatema; Kamal, Mohammad Shah (Medicine Today, 2014)
The study was undertaken to compare between surgery and radiotherapy in early carcinoma larynx (T1N0). 60 cases of early carcinoma larynx were selected purposive sampling technique from all the patients of carcinoma larynx admitted into Otolaryngology and Head-Neck Surgery Department of Bangabandhu Sheikh Mujib Medical University,Dhaka; Dhaka Medical College Hospital,Dhaka; Shaheed Suhrawardy Medical College Hospital, Dhaka; Taqwah Specialized Hospital,Dhaka from January 2010 to June 2011. Carcinoma of the larynx is the most common cancer affecting the head and neck region. The main aim of this study was to determine whether there was any difference in the two main therapeutic options. The secondary aim was to assess speech and voice quality in a small, randomized sample of patients from each treatment group. The subjects investigated were 60 patients with T1N0 squamous cell carcinoma of the larynx. 30 patients were treated by irradiation, and 30 were treated with surgery. The primary outcome measures were recurrence at the primary site, recurrence in the neck. The secondary outcome measure was speech and voice quality. Surgery included laser assisted partial laryngectomy and various minor procedures on the glottis, including cordectomy. Surgery was more likely to be carried out for supraglottic disease. Result showed 16.67% of the irradiation group had a primary site recurrence compared with 20.0% in the surgery group at 12th months (p = 0.59) and 6.67% of those who were treated with irradiation had a recurrence in the neck. 16.67% of patients in the surgery group had a recurrence in the neck (p < 0.05). There was no significant difference in primary site recurrence rates for the two treatment modalities, but regional recurrence was higher in the surgery group. Regarding speech and voice quality, radiotherapy was far superior to surgery. All patients in the radiotherapy group but only 3 of 10 in the surgery group were judged to have a good or normal voice (p = .0017). Both surgery and irradiation are equally effective at treating early laryngeal carcinoma but Speech and voice quality were significantly better in patients treated by irradiation than those treated by surgery. DOI: http://dx.doi.org/10.3329/medtoday.v26i1.21312 Medicine Today 2014 Vol.26(1): 41-45